Dynamic Changes in Lung Function and Imaging in Patients with COVID-19. (11th March 2022) - Ye, Lingyan; Hu, Bingyu; Lin, Shuangxiang; Chen, Meifang; Fang, Yicheng; He, Susu
Abstract : Purpose . To investigate the recovery of lung function and chest imaging in patients with COVID-19 three months after clinical cure and discharge and the correlation between them. Methods . This study collected 80 patients diagnosed with 2019-nCoV infection who were discharged from the Taizhou Public Health Medical Center in Zhejiang Province between January 31, 2020, and March 10, 2020. Lung function examinations and lung CT scans were performed at discharge and three months after discharge. The dynamic changes examined at discharge and three months after discharge were observed, and their correlation was analyzed. All data collection ended on June 25, 2020. Results . Among the 80 COVID-19 patients discharged from the hospital, the rate of abnormality indicated by lung CT images was 97.5%, mainly presenting as patchy shadows (95%), ground-glass shadows (75%), grid-like lesions, interlobular septal thickening or fiber strip shadows (30%), consolidation shadows, and nodules (10 cases each). At discharge, 72 patients (90%) had pulmonary dysfunction, 64 (80%) had restrictive ventilatory dysfunction, and 48 (60%) had small airway dysfunction. Three months after discharge, the rate of abnormality indicated by lung CT images was 12.5%. Eight cases (10%) showed residual patchy shadows, but the density was weak, and the scope was reduced. Two cases (2.5%) showed nodular shadows. Three months after discharge, 18 patients (22.5%) had residual restrictive ventilatory dysfunction, 28 patients (35%) had small airway dysfunction, and 32 patients (40%) had diffuse dysfunction. Moreover, patients with more severe chest imaging manifestations (bilateral lesions and ground-glass shadows combined with interstitial lesions) also had more obvious lung function impairment. Conclusion . Three months after being clinically cured, patients with COVID-19 had good chest imaging absorption and no residual fibrosis. Some patients had mild to moderate pulmonary dysfunction, mainly restricted ventilation dysfunction, small airway dysfunction, and diffuse dysfunction.